A Distributed Interactive Decision-Making Framework for Sustainable Career Development - Hallpike, Helen; Vallée-Tourangeau, Gaëlle; Van der Heijden, Beatrice (Frontiers in Psychology, 2022)
The purpose of this article is to present a new distributed interactive career decision-making framework (diCDM) in which person and context together determine the development of a sustainable career. We build upon recent theories from two disciplines: decision theory and career theory. Our new conceptual framework incorporates distributed stakeholders into the career decision-making process and suggests that individuals make decisions through a system of distributed agency, in which they interact with their context to make each career decision, at varying levels of participation, from proactive to reactive. We focus on two key career decision-making drivers originating from the person (exercising personal agency and seeking meaning), and two key drivers from the career context (making demands on an individual’s resources and affording scripts). This paper challenges the individual-driven approach to career development, and instead proposes that a process of distributed career decision-making takes place between each person and the various stakeholders, both individual and institutional, that also drive their career. Career seekers and counselors can use this framework to supplement an individual-focused approach and incorporate the role of distributed decision-makers in sustaining an individual’s career. Empirical research is needed to explore and test the applicability of the framework to career decisions in practice.